Without measure a Jack Widow thriller - Blade, Scott (Place of publication not identified Black Lion Media, 2017)
In this explosive whodunit, Jack Widow digs deep to uncover a horrifying terrorist network. Hitchhiking all night. No sleep. Jack Widow stops in a diner in a California mountain town. The town of Hamber has only two industries left: a small arms manufacturer and a forgotten Marine base. Wanting to drink coffee in peace, Widow can't ignore his cop senses warn him about a man, seated at another booth. The man is Arabic, Islamic, and a decorated Marine officer. But, there's something else. Something off. Something troubling. After a failed attempt to talk, Widow departs to find a motel bed, and sleep. But his head never makes the pillow because the local MPs show up, nearly banging down his door. Turns out after Widow sat with him, the Marine returned to base and shot five people -- dead, before killing himself. Witnesses saw Widow with him. Now, the MPs want to know why a decorated Marine, committed mass murder, moments after speaking to Widow. The locals want to blame radical Islam. The politicians want to blame gun culture. The media only care about the headlines. The White House wants nothing to do with it. Only, Jack Widow wants to find the truth. As he turns over rocks, Widow finds dark secrets crawling underneath.
111335
Keywords: Mass murder investigation -- California -- Fiction; Mass shootings -- California -- Fiction; Terrorism -- Fiction; Fiction; Thrillers (Fiction)